2010
DOI: 10.1002/uog.7694
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal antenatal Doppler velocimetry and cognitive outcome in very‐low‐birth‐weight infants at 2 years of age

Abstract: Objective To study neurodevelopmental outcome at 2 years of corrected age in very-low-birth-weight (VLBW) (≤ 1500 g) preterm infants with abnormal fetoplacental flow. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 50 publications
1
50
0
Order By: Relevance
“…Nevertheless, the same differences could not be documented at 11 years of age [27]. Leppanen et al [28] followed a group of very low birth weight infants until 2 years of age and found that abnormal neurological outcome was significantly associated with abnormal fetal MCA-PI; however, after adjusting for brain volume no significant association was longer observed. The conclusion was that intracranial Doppler parameters are related to the intracranial volume, and that reduced cranial volume has a higher association with abnormal neurological outcome.…”
Section: Early and Progressive Intrauterine Growth Restrictionmentioning
confidence: 84%
“…Nevertheless, the same differences could not be documented at 11 years of age [27]. Leppanen et al [28] followed a group of very low birth weight infants until 2 years of age and found that abnormal neurological outcome was significantly associated with abnormal fetal MCA-PI; however, after adjusting for brain volume no significant association was longer observed. The conclusion was that intracranial Doppler parameters are related to the intracranial volume, and that reduced cranial volume has a higher association with abnormal neurological outcome.…”
Section: Early and Progressive Intrauterine Growth Restrictionmentioning
confidence: 84%
“…In addition, no significant rise in major neonatal complications was depicted [25]. Conversely, it was also reported that neonates with EO-FGR and abnormal UA PI and brain vasodilatation had a significantly lower neurological performance than neonates with abnormal UA PI but without brain vasodilatation [28]. Further elaboration of findings of some studies that associated abnormal neurologic outcome and abnormal fetal MCA PI revealed no longer significant association after adjusting for brain volume [27].…”
Section: Discussionmentioning
confidence: 99%
“…There were 274 infants who met our inclusion criteria; they were born between 2001 and 2006 with a birth weight ,1501 g or between 2004 and 2006 with a gestational age (GA) ,32 weeks (very low GA), treated at Turku University Hospital, and from Finnishor Swedish-speaking families living in the catchment area to enable psychological assessment. 33 Infants with severe congenital anomalies or a diagnosed syndrome affecting their development were excluded. Forty-one (15%) died, 9 (4%) of the families refused to participate, and the number of later dropouts was 23 (10%).…”
Section: Study Subjectsmentioning
confidence: 99%